Mastermind is NP-Complete - Stuckman, Jeff; Zhang, Guo-Qiang (INFOCOMP Journal of Computer Science, 2006)
In this paper we show that the Mastermind Satisfiability Problem (MSP) is NPcomplete. Mastermind is a popular game which can be turned into a logical puzzle called the Mastermind Satisfiability Problem in a similar spirit to the Minesweeper puzzle. By proving that MSP is NP-complete, we reveal its intrinsic computational property that makes it challenging and interesting. This serves as an addition to our knowledge about a host of other puzzles, such as Minesweeper, Mah-Jongg, and the 15-puzzle.